Orientational Metaphor in Central Kurdish (Raparin Journal of Humanities (RJH), 2024)
This study is entitled "Orientational Metaphor in Central Kurdish". It attempts to explicate how non-spatial concepts are metaphorised in terms of various aspects of space in Central Kurdish. The main aim of the study is to interpret spatial metaphorical expressions that express the cognitive processes of meaning-making. The study adopts the Conceptual Metaphor Theory (CMT)within the framework of cognitive semantics. It deals with orientational metaphor as a specific type of conceptual metaphor. In cognitive semantics, language is a mirror of thought; linguistic expressions are manifestations of conceptual mappings structured in the mind. The data of the study is taken from ordinary everyday Kurdish. The data analysis illuminates the spatialization of a wide variety of abstract concepts through metaphorical uses of space. The study is in line with the cognitive linguists in that linguistic expressions that represent concepts are not semantically independent, as the Anglo-American philosophical tradition claimed, but are structured with respect to one another. Spatial concepts are first structured in thought in the form of a formula based on physical and socio-cultural experiences, and then expressed via linguistic metaphors; accordingly, metaphor is a cognitive phenomenon, it is in thought, not in language. It is patterns of thought that are echoed in patterns of language.